Plasma renin activity variation following admission predicts patient outcome in acute decompensated heart failure with reduced and mildly reduced ejection fraction. Issue 2 (February 2023) - Azuma, Kohei; Nishimura, Koichi; Min, Kyung-Duk; Takahashi, Kanae; Matsumoto, Yuki; Eguchi, Akiyo; Okuhara, Yoshitaka; Naito, Yoshiro; Suna, Sinichiro; Asakura, Masanori; Ishihara, Masaharu
Abstract: Background: Plasma renin activity (PRA) level at admission is reported to be a prognostic predictor of acute decompensated heart failure (ADHF) patients. Although PRA is affected during hospitalization by several factors including fluid volume and drug titration, whether the changes in PRA levels during hospitalization (ΔPRA) are associated with prognosis of ADHF patients are largely unknown. Purpose: Investigate the predictive impact of ΔPRA on the prognosis of ADHF patients with reduced ejection fraction (HFrEF) and mildly reduced ejection fraction (HFmrEF). Methods: Retrospectively analyzed consecutive 116 HFrEF and HFmrEF patients admitted for ADHF. PRA measurements were acquired at admission and at discharge. The primary outcome was a composite of cardiovascular death and HF re-hospitalization. Results: Out of 116 patients, 85 had PRA measurements both at admission and at discharge. Compared to admission, PRA level was significantly higher at discharge (0.8 (IQR 0.3–2.2) to 2.8 (IQR 1.0–7.2), p < 0.001). Tertiary groups ranked by PRA level on admission showed trend of poor prognosis in order of high, mid, and low PRA level (p = 0.07). On the contrary, PRA level at discharge significantly differentiated the prognosis and was poor in order of high, low, and mid (p = 0.026). Next, when the participants were divided into tertiary groups ranked by ΔPRA, prognosis worsened in the order of "minimal", "decreasing", and the "increasing" tier. Cubic splines analysis also indicate a similar tendency. Conclusions: In ADHF patients with HFrEF and HFmrEF, patients with minimal ΔPRA showed the better prognosis over the those with either increasing or decreasing. Highlights: In HFmrEF or HFrEF patients admitted for AHF, PRA level is significantly elevated at discharge compared to admission. This is the first report indicating that amount change in PRA level during hospitalization are associated with prognosis. Minimal change in PRA level during hospitalization was associated with better outcome.